Extracoporeal shockwave treatment decreases pain, functional limitations and medial collateral ligament thickness in subjects aged 50-70 years with knee osteoarthritis - Kokok, Andwi Setiawan; Tamin, Tirza Z; Murdana, Nyoman; Widyahening, Indah Suci (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundPain from knee and hip osteoarthritis (OA) can have a significant impact on the physical function and quality of life of affected individuals worldwide. The objective of this study was to evaluate the effect of extracorporeal shockwave therapy (ESWT) on pain, flexibility, function, and medial collateral ligament (MCL) thickness in knee osteoarthritis (KOA). MethodsA study of quasi experimental design was performed involving 15 subjects aged 50 – 70 years with Kellgren-Lawrence grade 2-3 KOA. All subjects were evaluated regarding baseline -pain using visual analogue scale (VAS), range of motion (ROM), functional outcome using Western Ontario and McMaster Universities Arthritis Index (WOMAC), and MCL size. Extracorporeal shock wave therapy was given 3 times, at baseline, and 4 and 8 weeks after intervention. All subjects were given 4000 shocks at intensities of 1.5 – 4 Bar (raised gradually) per session. The shocks were given in the supine position, knee flexed 90o, without topical anesthetic. Statistical analyses were conducted using a dependent t-test. ResultsAfter 8 weeks of intervention, ESWT significantly improved pain score (p<0.01), WOMAC (p<0.01) and MCL thickness (p<0.01) in patients with OA of the knee. However, there was no significant difference in knee ROM, both for degree of flexion and extension (p>0.05). ConclusionThe use of ESWT for treatment of knee OA had a beneficial effect on pain relief, function outcome and MCL thickness. However, there remains a lack of clarity regarding the frequency and dosage levels of ESWT required to achieve maximum improvement.